2019
DOI: 10.26719/emhj.19.012
|View full text |Cite
|
Sign up to set email alerts
|

I am HIV-positive, but I am a human being: qualitative study on experiences of stigma in health care centres in the Islamic Republic of Iran

Abstract: Background: People living with HIV can have many health problems and may face difficulties when seeking health care because of stigma and the inappropriate behaviour of health care staff. Aims: This study aimed to assess the problems people living with HIV face when seeking health care in the Islamic Republic of Iran. Methods: A qualitative study was conducted with 10 people living with HIV who were members of the positive fellowship club of the Imam Khomeini Hospital in Tehran, Islamic Republic of Iran. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…This is particularly important for marginalized PWID whose sole source of obtaining sterile needles and condoms is through government-funded harm reduction services. A limited body of evidence suggest that similar to several international settings (Van Boekel, Brouwers, Van Weeghel, & Garretsen, 2013), socio-cultural stigma (e.g., negative attitudes towards PWID and their families) within several communities across Iran creates barriers to accessing important health and harm reduction services and therefore prevent PWID from getting the help they need (Abedinia, Rasoolinajad, Noorbala, & Badie, 2019;Amin-Esmaeili et al, 2016;Deilamizade, Moghanibashi-Mansourieh, Mohammadian, & Puyan, 2019;Karamouzian, Akbari, Haghdoost, Setayesh, & Zolala, 2015;SeyedAlinaghi et al, 2013;Zolala, Mahdavian, Haghdoost, & Karamouzian, 2016). Furthermore, while Iran's drug policy has shifted from complete criminalization of substance use to a more evidence-based -yet heavily medicalized-approach in the past 40 years, PWID continue to face structural stigma and discrimination (e.g., facing ignorance and receiving substandard care) when seeking healthcare and harm reduction services (Karamouzian et al, 2015;Rahmati-Najarkolaei et al, 2010;Tavakoli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for marginalized PWID whose sole source of obtaining sterile needles and condoms is through government-funded harm reduction services. A limited body of evidence suggest that similar to several international settings (Van Boekel, Brouwers, Van Weeghel, & Garretsen, 2013), socio-cultural stigma (e.g., negative attitudes towards PWID and their families) within several communities across Iran creates barriers to accessing important health and harm reduction services and therefore prevent PWID from getting the help they need (Abedinia, Rasoolinajad, Noorbala, & Badie, 2019;Amin-Esmaeili et al, 2016;Deilamizade, Moghanibashi-Mansourieh, Mohammadian, & Puyan, 2019;Karamouzian, Akbari, Haghdoost, Setayesh, & Zolala, 2015;SeyedAlinaghi et al, 2013;Zolala, Mahdavian, Haghdoost, & Karamouzian, 2016). Furthermore, while Iran's drug policy has shifted from complete criminalization of substance use to a more evidence-based -yet heavily medicalized-approach in the past 40 years, PWID continue to face structural stigma and discrimination (e.g., facing ignorance and receiving substandard care) when seeking healthcare and harm reduction services (Karamouzian et al, 2015;Rahmati-Najarkolaei et al, 2010;Tavakoli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Implemented studies in Iran [ 16 , 45 ] revealed that stigma would be a main barrier for utilization of healthcare services by PLHIV and it might affect their quality of life. Hence, reducing stigma could be an effective strategy to improve their HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study implemented in Tehran using WHOQoL-BREF showed that patients with HIV are faced with many problems when trying to get medical treatment for the disease and other conditions because of stigma, lack of awareness, incomplete information on how the disease is transmitted, or intense fear of personnel and health professionals [ 16 ]. Experiencing HIV-related stigma and discrimination among PLHIV is associated with a number of adverse health outcomes including feelings of anxiety, fear, frustration, depression, stress, shame, rejection, and self-isolation as well as limited access to treatment and healthcare services [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bunun yanı sıra, HIV taşıyıcısı olan bireylerin kendinden utanmaları gerektiğine inanma şeklinde de görülmektedir. Bu stigmatize tutum ve davranışlar HIV pozitif bireylerin yalnız hissetme, utanç duyma, "mikroplu" hissetme, toplumdan izole olmasına neden olabilmektedir (3,5,6). Yaşanan bu bakışın ve ayrımcılığın süreklileşmesi, bu hastaların psikososyal sağlık sorunları yaşamasına ve hatta intihar etmelerine neden olabilmektedir.…”
Section: Introductionunclassified